SLANG EXPRESSIONS IN ZOOTOPIA: Insights For EFL Vocabulary Learning A Qualitative Analysis for Indonesian EFL Classrooms - Alifah Setiyawati; Abdul Ngafif; Zulia Chasanah (Varied Knowledge Journal, 2026)
Vocabulary development plays an important role in English as a Foreign Language (EFL) learning because it supports learners’ ability to understand and produce meaningful communication. However, classroom practices still rely heavily on textbook-based materials and provide limited exposure to authentic spoken English. Informal language features such as slang expressions are often overlooked in vocabulary instruction, although they frequently appear in daily communication. This study investigated slang expressions in the animated movie Zootopia and explored their potential contribution to EFL vocabulary learning. This study employed a qualitative descriptive design using documentation and note-taking techniques based on the movie script and subtitles to ensure contextual accuracy. The data were analyzed through qualitative content analysis to identify and classify slang expressions according to their linguistic forms, communicative functions, and contextual meanings. The findings revealed 30 slang expressions categorized into reduced forms, informal lexical slang, idiomatic expressions, and address terms. Informal lexical slang and reduced forms were the most dominant categories, showing the frequent use of conversational language in the movie. In addition, these expressions reflected pragmatic and sociolinguistic meanings that supported learners’ understanding of authentic spoken English. The study suggests that animated movies can serve as effective media for contextual vocabulary learning by providing authentic exposure to natural spoken English and supporting learners’ awareness of natural language use in EFL classrooms.